Membrane proteins modulate the bilayer curvature in the bacterial virus Bam35. - Laurinmäki, P; Huiskonen, J; Bamford, D; Butcher, S (2005)
Biological membranes control the flow of molecules into and out of cells, and they transmit information about the milieu. Structural studies of membrane-containing viruses provide one way to study these membranes in situ. Cryo-electron microscopy and image reconstruction of bacteriophage Bam35 to 7.3 A resolution revealed a membrane bilayer constrained within an icosahedrally symmetric pseudo T = 25 capsid. A total of 60 large transmembrane protein complexes affect the curvature and thickness of the membrane. Here, we describe these membrane parameters quantitatively. Furthermore, we show that Bam35 differs from bacteriophage PRD1 in these parameters, even though the two viruses share the same principles of capsid architecture. Most notably, each virus possesses a tape measure protein suggesting a general mechanism for capsid size determination in icosahedral viruses.